Phase-pure two-dimensional FeₓGeTe₂ magnets with near-room-temperature Tc - Nair, Govindan Kutty Rajendran (2022)
Two-dimensional (2D) ferromagnets with out-of-plane (OOP) magnetic anisotropy are potential candidates for realizing the next-generation memory devices with ultra-low power consumption and high storage density. However, a scalable approach to synthesize 2D magnets with OOP anisotropy directly on the complimentary metal-oxide semiconductor (CMOS) compatible substrates has not yet been mainly explored, which hinders the practical application of 2D magnets. This work demonstrates a cascaded space confined chemical vapor deposition (CS-CVD) technique to synthesize 2D FexGeTe2 ferromagnets. The weight fraction of iron (Fe) in the precursor controls the phase purity of the as-grown FexGeTe2. As a result, high-quality Fe3GeTe2 and Fe5GeTe2 flakes have been grown selectively using the CS-CVD technique. Curie temperature (TC) of the as-grown FexGeTe2 can be up to ∼ 280 K, nearly room temperature. The thickness and temperature-dependent magnetic studies on the Fe5GeTe2 reveal a 2D Ising to 3D XY behavior. Also, Terahertz spectroscopy experiments on Fe5GeTe2 display the highest conductivity among other FexGeTe2 2D magnets. The results of this work indicate a scalable pathway for the direct growth and integration of 2D ternary magnets on CMOS-based substrates to develop spintronic memory devices. [Figure not available: see fulltext.].